The Paris library - Skeslien Charles, Janet (Two Roads, 2021)
Paris, 1939. Odile Souchet is obsessed with her new job at the American Library in Paris. When war is declared, the Library is determined to remain open. But then the Nazis invade Paris, and everything changes. 1983. Lily grows close to her neighbour Odile, discovering they share the same love of language. But as Lily uncovers more about Odile's mysterious past, she discovers a dark secret